The Anatomy of Disgust in Criminal Law - Kahan, Dan M. (1998)
My goal in this review is to call attention to a defect in the dominant theories of criminal law and to identify a resource for remedying it. The defect is the absence of a sophisticated account of how disgust does and should influence legal decisionmaking. The corrective resource is William Miller's The Anatomy of Disgust. To make my claims more vivid, consider two stories. Both involve men who were moved to kill by disgust toward homosexuality